Sideshow : ten original tales of freaks, illusionists, and other matters odd and magical - Noyes, Deborah (Somerville, Mass. : Candlewick Press, 2009)
Collects ten humorous and eerie stories about magicians, psychics, monsters, and freaks both inside and outside of the circus.
The bearded girl / Aimee Bender -- Those psychics on TV / Vivian Vande Velde -- Year of the rat / Danica Novgorodoff -- The mummy's daughter / Annette Curtis Klause -- When God came to Kathleen's garden / David Almond -- The shadow troupe / Shawn Cheng -- Cat calls / Cynthia Leitich Smith -- The bread box / Cecil Castellucci -- Living curiosities / Margo Lanagan -- Jargo! / Matt Phelan.
Booklist.
Kirkus Review.
School Library Journal.
Young Adult
Keywords: Curiosities and wonders -- Juvenile fiction; Short stories, American; Curiosities and wonders -- Fiction; Short stories; Curiosities and wonders -- Fiction; Short stories